The Reimaging of Hindu Mythology: A study of Naga Myth in ‘The Secret of the Nagas’ - N.Navaneetham; Dr. C. Arun (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This paper explores Amish Tripathi’s novel The Secret of the Nagas (2011), which reinterprets the Hindu myth of the Nagas. As the second book in Tripathi's Shiva Trilogy, it blends elements of modern fantasy with insights from the ancient text Shivapurana, using mythology to address contemporary issues. In this installment, the protagonist, Shiva, embarks on a crucial journey to uncover the reality of the Nagas. In Hindu mythology, Nagas are traditionally depicted as serpents. However, in Tripathi’s narrative, they represent individuals with physical deformities who are deemed inauspicious by the inhabitants of the Sapt-Sindhu region. As a result, they face social exclusion and are compelled to live along the banks of the Narmada River, with Panchavati serving as the capital of their territory, Nagaland. Through the Shiva Trilogy, Tripathi examines the deep-rooted beliefs of the Hindu community, highlighting their intricate connections with the societal laws and norms of that era.